Socio-Demographic and Occupational Characteristics with Unsafe Action to Brick Making Worker (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Unsafe actions are one of the causes of accidents that endanger workers themselves and others. Many work accidents occur in the informal sector, one of which is brick printing. Brick-making workers face dangers at every stage of their work, such as falls, slips and trips. The results of the preliminary study showed that 60% of workers work with unsafe actions, for example workers still use damaged work equipment and workers lift loads with inadequate tools, while 40% of them work safely. This research aims to analyze the relationship between socio-demographic characteristics gender, age and workload with unsafe actions in brick kiln workers, Candisari, Demak. The research used an observational research design conducted on 55 workers at the Candisari brick factory, Demak. This research was conducted through interviews using an unsafe action questionnaire. The variables used in the research are gender, age, length of work and length of service using questionnaires, workload using pulse measurements. Result, Univariate analysis showed that there were more male workers than female workers, namely 50.9% with an average age of 44 years, 8 years of work, 8 hours of work and a medium workload. The average score for unsafe actions is 17.29, which means that the average worker commits unsafe actions. The chi aquare test results show a relationship between gender (p=0.004), workload (p=0.035) and unsafe actions, the Pearson test results show a relationship between age (p=0.001) and unsafe actions. Conclusion the research results show that there is a relationship between age, gender, and workload.